The Politics of the Urban Sustainability Concept - Denpaiboon, Chaweewan (Journal of Architectural/Planning Research and Studies (JARS), 2022)
As an academician in urban environmental planning and management, I understood that urban politics is politics in and about cities. This term refers to the diverse political structure that occurs in urban areas where there is diversity in both culture and socio-economic status. Urban politics are political science that falls into the field of urban studies, which incorporates many aspects of cities, suburbs, and urbanization. Recent trend in urban politics is in assuring sustainable urban development where political leaders, public representatives, and urban local government play the lead role in constructing any planning process which is focusing accessibility to resources, equity, facilities and poverty including working for the production and economic opportunities in order to decent guaranty of life for sustainable development.